2019
DOI: 10.1029/2019jd030803
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Lows in Southern Africa: Tracks, Rainfall Contributions, and the Role of ENSO

Abstract: Southern African tropical lows are synoptic‐scale cyclonic vortices that propagate westward across southern Africa in the Austral summer. They strongly influence local rainfall and aggregate in the climatological December, January, and February mean to form the Angola Low. In this study, tropical lows are identified and tracked using an objective feature tracking method. The statistics of tropical low tracks over southern Africa are presented and compared across three reanalysis products. Findings are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Howard and Washington (2018) have shown that the characteristics of the AL can be separated into heat and tropical low phases. Howard et al (2019) further investigated the relationship between the tropical low activity and precipitation over southern Africa. Their two circulation patterns of tropical low activity across the southern African continent agree with the two dominating clusters during the Msimu Rains in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Howard and Washington (2018) have shown that the characteristics of the AL can be separated into heat and tropical low phases. Howard et al (2019) further investigated the relationship between the tropical low activity and precipitation over southern Africa. Their two circulation patterns of tropical low activity across the southern African continent agree with the two dominating clusters during the Msimu Rains in our work.…”
Section: Discussionmentioning
confidence: 99%
“…The green color indicates grid cells where significantly positive anomaly correlation is attributable to negative ENSO teleconnection. They appear in northern South America and southern Africa, where negative ENSO teleconnection is known to exist (Cai et al, 2020;Howard et al, 2019) and also in parts of Far East and Alaska. There are also grey areas where significantly positive anomaly correlation is not attributable to ENSO teleconnection.…”
Section: Attribution At the Global Scalementioning
confidence: 99%
“…The green color indicates grid cells where significantly positive anomaly correlation is attributable to negative ENSO teleconnection. They appear in northern South America and southern Africa, where negative ENSO teleconnection is known to exist (Howard et al, 2019;Cai et al, 2020) and also in parts of Far East and Alaska. There are also gray areas where significantly positive anomaly correlation is not attributable to ENSO teleconnection.…”
Section: Attribution At the Global Scalementioning
confidence: 99%